The challenge of managing knowledge transfer among technology firms in Malaysian Technology Parks - Mhd. Sarif, Suhaimi (2010)
The study examines the management of knowledge transfer among technology firms in Malaysian technology parks by using the concept of “macro stickiness.” The concept uses literature in the field of innovation studies, in which governments have been identified as major contributors. The study examines the perceptions of a variety of informants of stickiness in knowledge transfer among technology firms in Malaysian technology parks. The study interviewed fifty (50) informants, who included policy makers, government officers, and senior executives of technology firms in Malaysian technology parks. The preliminary findings indicated that policy makers and government confirmed that they cannot go away from previous policy documents when formulated policies for technology incubation that based on three major elements: enhancement of national unity, intensification of foreign direct investment and expectation of sound economic growth. Such actions do not sufficiently promote knowledge transfer among technology firms in the incubation facilities because technology firms are motivated to gain short term profits instead of developing indigenous technology.